Iridium‐Catalyzed Annulation Reactions of Thiophenes with Carboxylic Acids: Direct Evidence for a Heck‐type Pathway. (23rd April 2018) - Tan, Guangying; You, Qiulin; Lan, Jingbo; You, Jingsong
Abstract: The functionalization of thiophenes is a fundamental and important reaction. Herein, we disclose iridium‐catalyzed one‐pot annulation reactions of (benzo)thiophenes with (hetero)aromatic or α, β‐unsaturated carboxylic acids, which afford thiophene‐fused coumarin‐type frameworks. Dearomatization reactions of 2‐substituted thiophenes with α, β‐unsaturated carboxylic acids deliver various thiophene‐containing spirocyclic products. The occurrence of two interconnected reactions provides direct evidence for a Heck‐type pathway. The mechanistic scenario described herein is distinctly different from the SE Ar and concerted metalation–protodemetalation (CMD) pathways encountered in the well‐described oxidative C−H/C−H cross‐coupling reactions of thiophenes with other heteroarenes. Abstract : In einem Rutsch : Die Iridium(III)‐katalysierte Anellierung von (Benzo)thiophenen mit (hetero)aromatischen oder α, β‐ungesättigten Carbonsäuren führt zu Coumarin‐artigen und spirocyclischen Gerüsten. Für diese Reaktionen wird ein Heck‐artiger Mechanismus vorgeschlagen.